2018
DOI: 10.3390/ijerph15081602
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Population Growth in Chinese Floodplains from 1990 to 2015

Abstract: Although China suffers from frequent and disastrous floods, the spatiotemporal pattern of its population living in the floodplain (PopF) is still unknown. This strongly limits our understanding of flood risk and the effectiveness of mitigation efforts. Here we present the first quantification of Chinese PopF and its dynamics, based on newly-available population datasets for years 1990, 2000, 2010, and 2015 and on a flood map. We found that the PopF in 2015 was 453.3 million and accounted for 33.0% of the total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…The results derived from the above analyses align with the findings in previous studies. Fang et al (2018) reported that China's population living in floodplains increased at an annual rate of 1.3% from 1990 to 2015, which was faster than in other regions of the country. Our analyses also yield a similar annual growth rate of approximately 1.2% in the flood hazard areas from 1995 to 2015 (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results derived from the above analyses align with the findings in previous studies. Fang et al (2018) reported that China's population living in floodplains increased at an annual rate of 1.3% from 1990 to 2015, which was faster than in other regions of the country. Our analyses also yield a similar annual growth rate of approximately 1.2% in the flood hazard areas from 1995 to 2015 (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Sajjad et al (2018) predicted that the number of people exposed will double in China's coastal areas that are under current sea level rise by 2100, reaching a total of 10 million. Fang et al (2018) and Du et al (2018) conducted research to investigate the changes of population and built-up land in China's flood-prone areas. Miao et al (2018) identified the provinces south of the Yellow River as the regions with relatively higher population vulnerability to landslides.…”
Section: Introductionmentioning
confidence: 99%
“…However, efforts to restore and protect open water, such as lakes and ponds, deteriorated over time (Cheng and Li, 2015), and by 2015 there are still 406 polders in the main channels of Yangtze River and 133 polders in the Dongting-and Poyang lake regions, with a total population of 1.9 million (Ministry of Water Resources, 2015). Nationwide, the population living in floodplains increased by 1.1% per year over the period 1990-2015, which is much faster than the population increase outside floodplains (0.4% per year) (Fang et al, 2018).…”
Section: China's Response To the 1998 Floodmentioning
confidence: 92%
“…Flood management in China, and in particular in urban areas, could be better prepared for these trends. Urbanization in Chinese floodplains continues to increase, for example at rate of 20,600 km 2 /year over the period 1998 and 2015 (Du et al, 2018), and by 2050, it is expected that 80.0% of China's total population will live in cities, rising from 55.5% in 2015 (Population Division of United Nations, 2018)with an additional of 172.8 million people in floodplains (Fang et al, 2018). These numbers will probably be even higher due to the ending of the 'one-child' policy.…”
Section: Future Challenges To Flood Management In Chinamentioning
confidence: 99%
“…Exposure can be defined as the depreciated or replacement value of the tangible physical assets in hazard-prone areas [3,4]. Flood risk under climate change and socioeconomic change is a great challenge for flood risk management [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%